The role of polymorphism of genes eotaxin (–384) and CCR3 (–51) in formation of blood eosinophilia under pulmonary tuberculosis - K. O. Miheeva; Yu. V. Kolobovnikova; O. I. Urazova; V. V. Novitsky; O. V. Filinyuk; M. D. Goncharov; I. O. Naslednikova (Бюллетень сибирской медицины, 2012)
With attracting contemporary molecular-genetic and immunological research methods, it has been established that blood eosinophilia under pulmonary tuberculosis is mediated by hypersecretion eotaxin. Susceptibility to the emergence of eosinophilic blood reaction under tubercular infection is associated with the allele G and homozygous genotype GG of the polymorphic region A-384G of the gene eotaxin as well as with allele С and homozygous genotype СС polymorphism T-51C of the gene ССR3.